FATALOZA NUR RAZAK : PROFIL PEREMPUAN PENERIMA BANTUAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI NAGARI LALANG PANJANG KECAMATAN AIR PURA KABUPATEN PESISIR SELATAN - Ningsih, Feni Suarti; Naldi, Hendra; Kharles, Kharles (Pendidikan Sejarah, 2014)
Woman Profile as the receiver a helping hand of Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri in Lalang Panjang, Air Pura, Pesisir Selatan. History Education Program. STKIP PGRI West Sumatra. Padang 2014. This thesis discusses about Woman Profile as the receiver a helping hand of Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri in Lalang Panjang, Air Pura, Pesisir Selatan. This study about Fataloza Nur Razak who receives a helping hand PNPM mandiri. This study very interesting to discuss because it can seeÂ  the process of program and impact to peopleâs live who is be member of that program, one of them is Fataloza Nur Razak. To facilitate this research, the problem can be formulated as follows: (1) How is the background of life Fataloza Nur Rozak before and after got the assistance program. (2) How does the socio-economic life of Fataloza Nur Rozak before and after got that program. The method that used in this research is historical method performed with several stages. The first is heuristic which are interview, documentation, and library research. The researcher doing interview with Fataloza Nur razak , her husband and two her children. The researcher also gets more information from many sources such as book and thesis in Regional Library, Unand Library, UNP Library and STKIP PGRI Library that has related with the topic. The second stage is source criticism, which the researcher verify the data in external critic and internal critic.Â Â  The third stage is analysis, systematic and interpretation. In the last stage, the researcher reports the result of research. Based on the research the researcher describes the results are, the existence of PNPM Mandiri give benefits for members especially for Fataloza Nur Razakâs economic life, and Fataloza Nur Razakâs life better after be member of PNPM Mandiri.